EXTRACTION AND IDENTIFICATION OF SECONDARY METABOLITE COMPOUNDS OF SEA CUCUMBER (Stichopus ocellatus) - Sherrin Sherrin; Mery Sukmiwati; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTStichopus ocellatusis one kind of sea cucumbers, invertebrate animals, there were widespread in Indonesian waters. The sea cucumbers in this study were taken from Lengkang Island, Batam. This study aimed to find out the secondary metabolite compounds in sea cucumber extract. This research was conducted through several stages, namely sea cucumbers extracted using maceration method with ethanol solvents for 3 x 24 hours with different sample and solvent comparisons (1:1, 1:3, and 1:5). Identification was carried out by observingthe color reactions, precipitation, and froth. The result showed that the extract obtained was characterized like a viscous extract with yellow-brown color and fishy smell. The yield of sea cucumber extract produced by using those each solvent ratio were 1.46%, 2.37%, and 3.33%, respectively. Secondary metabolite compounds identified in sea cucumber extract were alkaloids, phenolics, and saponins.Keywords: Sea Cucumbers, Extraction, Metabolite Compounds, Yield